2014
DOI: 10.5101/nbe.v6i2.p60-66
|View full text |Cite
|
Sign up to set email alerts
|

CIK Cell Therapy for Solid Tumor

Abstract: In recent years, the clinical trials on applying cytokine induced killer (CIK) cells to solid tumor therapy have been launched worldwide. CIK cells are a heterogeneous subset of ex-vivo expanded T lymphocytes, they present a mixed T-NK phenotype and are endowed with a MHC-unrestricted antitumor activity, which have showed great advantages in clinical treatment compared with other adoptive immunity therapies, therefore, they are more and more widely used in adoptive immunotherapy of tumors. CIK cells can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Human CIK cells were expanded from peripheral blood collected from the healthy people in our Laboratory [17]- [22]. All individuals provided informed consent for blood donation according to a protocol approved by the internal review board and ethic committee.…”
Section: Preparation and Identification Of Human Cik Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human CIK cells were expanded from peripheral blood collected from the healthy people in our Laboratory [17]- [22]. All individuals provided informed consent for blood donation according to a protocol approved by the internal review board and ethic committee.…”
Section: Preparation and Identification Of Human Cik Cellsmentioning
confidence: 99%
“…Some reports show that human CIK cells can target in vivo tumor tissues [17]- [22]. However, a lot of reports showed that CIK cells kill tumor cells via releasing some special factors [47,48].…”
Section: Cik Cells Labeled With Pegylated Aunprs For Targeted Fluoresmentioning
confidence: 99%
See 1 more Smart Citation